Determination of the soil and potential type of soil collapse of the Intiorko health place district of Ciudad Nueva, department of Tacna-2017 - Flore Mello, Alfonso Oswaldo (2018)
The type of soil and soil collapse potential of the Intiorko Health Post, district of Ciudad Nueva, department of Tacna, was investigated. Applied research was developed, due to the use of preexisting knowledge in research and technical standards, analyzing existing information close to the study area, developing standard tests for the identification of collapsible soils, as well as laboratory and in situ collapse tests. The load test with collapse of the soil structure to determine the potential for collapse. It was identified that the physical, mechanical and chemical properties contribute to the collapsible structure of the soil, this due to the low natural density, liquid limit, high ratio of voids and total soluble salts; Likewise, he identified that at the pressure of 1.00 kg / cm2 collapse problems are not generated, while with 2.00 kg / cm2 the problem is moderate; It was also identified that the settlement by collapse corresponds to 90% of the immediate settlement product of the in situ load test with collapse. The soil collapse potential of the Intiorko Health Station, in Ciudad Nueva, Tacna department, for a permissible load capacity of 1.00 kg / cm2 is moderate, because the physical, mechanical and chemical properties contribute to the potential for collapse and this pressure the angular distortion does not cause cracking in walls.